Modeling cancer-microbiome interactions in vitro: a guide to co-culture platforms - Moskal, Kamil; Khurana, Nimisha; Siegert, Luisa; Lee, Ye Seul; Clevers, Hans; Elinav, Eran; Puschhof, Jens (International journal of cancer, 2025)
The biology of cancer is characterized by an intricate interplay of cells originating not only from the tumor mass, but also its surrounding environment. Different microbial species have been suggested to be enriched in tumors and the impacts of these on tumor phenotypes is subject to intensive investigation. For these efforts, model systems that accurately reflect human-microbe interactions are rapidly gaining importance. Here we present a guide for selecting a suitable in vitro co-culture platform used to model different cancer-microbiome interactions. Our discussion spans a variety of in vitro models, including 2D cultures, tumor spheroids, organoids, and organ-on-a-chip platforms, where we delineate their respective advantages, limitations, and applicability in cancer microbiome research. Particular focus is placed on methodologies that facilitate the exposure of cancer cells to microbes, such as organoid microinjections and co-culture on microfluidic devices. We highlight studies offering critical insights into possible cancer-microbe interactions and underscore the importance of in vitro models in those discoveries. We anticipate the integration of more complex microbial communities and the inclusion of immune cells into co-culture systems to more accurately simulate the tumor microenvironment. The advent of ever more sophisticated co-culture models will aid in unraveling the mechanisms of cancer-microbiome interplay and contribute to exploiting their potential in novel diagnostic and therapeutic strategies.
Online veröffentlicht: 23. Dezember 2024
Gesehen am 24.03.2025